2005
DOI: 10.1016/j.ijgo.2004.12.043
|View full text |Cite
|
Sign up to set email alerts
|

A tool for assessing ‘readiness’ in emergency obstetric care: The room‐by‐room ‘walk‐through’

Abstract: This article presents a tool that can be used to assess the readiness of a health facility to provide emergency obstetric care. The 'walk-through' tool is a checklist that follows the physical path that a woman and her caregivers might follow. The items on the checklist are critical to an enabling environment in which skilled providers can save lives. The article explains how the tool can be used and by whom, and it describes several experiences in the field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 6 publications
(8 reference statements)
0
22
0
1
Order By: Relevance
“…Mozambique was no exception and resistance to investing in infrastructure was encountered at multiple levels. Ideally renovations should be planned and initiated as soon as possible so that by the time staff have been trained and equipment and supplies have been distributed, both staff and patients will benefit from these visible and functional improvements [14]. Renovations were slow to start but by early 2004 all renovations were complete.…”
Section: Improvements In Infrastructurementioning
confidence: 99%
See 1 more Smart Citation
“…Mozambique was no exception and resistance to investing in infrastructure was encountered at multiple levels. Ideally renovations should be planned and initiated as soon as possible so that by the time staff have been trained and equipment and supplies have been distributed, both staff and patients will benefit from these visible and functional improvements [14]. Renovations were slow to start but by early 2004 all renovations were complete.…”
Section: Improvements In Infrastructurementioning
confidence: 99%
“…The bwalk-throughQ tool was introduced and modeled by AMDD staff as a method of assessing readiness in the facility [14]. This tool was designed to be used for frequent if not daily assessments by an external supervisor or internally by senior staff.…”
Section: Quality Improvement Activitiesmentioning
confidence: 99%
“…It is important, therefore, to measure facility level data [27]. Research has shown that in order to reduce maternal mortality, three facility level components need to be in place: application of good quality medical technology and use of skilled clinical providers; good management and organization within the facility including personnel, equipment, drugs and supplies; and a respect for human rights efforts to improve functioning at the facility level [28,29]. …”
Section: Introductionmentioning
confidence: 99%
“…This framework serves as a blueprint for organizing program priorities and has also proved useful in conflict settings [29,30]. As a first step in the process of improving RH care, it is important to have a clear understanding of the service delivery environment.…”
Section: Introductionmentioning
confidence: 99%
“…Health centres and hospitals play a crucial role in reducing maternal mortality and morbidity by providing respectively Basic Emergency Obstetric and Newborn Care (BEmONC) and Comprehensive Emergency Obstetric and Newborn Care (CEmONC) [5-7]. The readiness of hospitals to provide CEmONC depends on the availability of qualified human resources, infrastructure like surgical theatres, and supplies like drugs and blood for transfusion [8]. Recent studies carried out in Africa and Asia pointed out the limited availability of caesarean section and blood transfusion services in many hospitals [9-11].…”
Section: Introductionmentioning
confidence: 99%